Identifikasi Senyawa Sitotoksik Karang Lunak Sarcophyton sp. Dari Perairan Pulau Panggang Taman Nasional Kepulauan Seribu - SRI ISWANI; DUDI TOHIR; HEDI INDRA JANUAR (Fakultas Farmasi Universitas Pancasila, 2014)
This research aimed to identify the cytotoxic compounds from Sarcophyton sp. which dominated the coral reefs area at Panggang Islands water, Seribu Islands National Parks. Preparative chromatography and bioassay MCF-7 cell lines guided fractionation had been used in isolation process of cytotoxic compounds. Moreover, UV-VIS, HR-ESI-MS, and 400 MHz NMR spectroscopy methods had been used as the technique to elucidated all of the active compound. The result of this study found three active cytotoxic compounds. These compounds were Sarcophytol (IC50 36,041 ppm), sarcophytol (IC50 71,03 ppm), and sarcophyhtolide (IC50 67,227 ppm). Ecologically, these results showed that Sarcophyton from Panggang Islands coral reefs waters produced a diversed bioactive compound so this organism can win the spatial competition, detterant predation, and dominate in this area.